ANALYSIS OF BULLYING IN WONDER FILM BY STEPHEN CHBOSKY (A PYSCHOLOGICAL APPROACH) - Gae, Yohanes; Kara, Yuliana M D K (Lantern: Journal of Language and Literature, 2025)
This research aimed at analyzing the types of bullying and the method of intervening bulying cases experienced by Auggie as reflected in Wonder film by Stephen Chbosky. In this research the Writer used the qualitative descriptive method. The research was used some theories, they are Bullying theory by Jacob Gordon (2018) and the method of intervening bullying cases by Ken Rigby (2010). The data using from this research is from Wonder film (2017) by Stephen Chbosky. The result of this research show that there are three (3) types of bullying that Auggie receives and six (6) method of intervening Bullying cases found in Wonder film. The types of bullying that Auggie received were verbal bullying, physical bullying and cyber bullying. While the method of intervening bullying cases are traditional disciplinary, strengthening the victim, mediation, restorative practices, support group, and shared concern methods.